Intensive care unit admission of obstetrics cases in a tertiary care centre - Kaveri; Doddamani, Usha; Tasneem, Aaliya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: ICU admissions is on the rise in pregnant women. These must be handled by obstetricians and intensivist. Methods: This retrospective observational study was conducted at the Gulbarga Institute of Medical Sciences to analyze obstetric outcomes and complications among patients admitted to the obstetric intensive care unit (ICU) from January to June 2024. The study included 69 women out of approximately 3651 deliveries, resulting in an ICU admission rate of 1.88%. Results: Patient demographics revealed a predominance of younger women under 25 years, with the majority being in their first and second pregnancies. Antepartum admissions comprised 69.5% of cases, with hypertensive disorders of pregnancy and postpartum hemorrhage being the primary reasons for ICU admission. A range of interventions was administered, including anticonvulsants, blood transfusions, and mechanical ventilation. The study recorded 12 maternal deaths, primarily due to hemorrhage, hypertensive disorders, and sepsis, pointing to significant challenges within maternal healthcare management in critical settings. Conclusions: The findings underscore the necessity for enhanced patient management strategies to address the identified complications and improve maternal outcomes in high-risk obstetric populations.